Unleashing the Sounds of Silence: Hong Kong’s Story in Troubled Times - Andrea Riemenschnitter (Global Storytelling)
Hong Kong’s story is difficult to tell, commented Leung Ping-kwan (1949–2013) in consideration of the city’s complicated historical configuration as well as the aesthetic reflection on the same by the writers and artists that have come to shape and promote the colonial city’s unique culture. Confronting the post-handover government’s suppression of democratic decision-making with massive street protests, the next generation of cultural producers continues to critically interrogate, contest, and subvert the official genealogy and nationalist master narrative. In response to the various factors contributing to the ongoing silencing of the city’s critical voices, many artists, directors, and writers have turned to (absent) sound as the aesthetic signifier of the sociopolitical turn from hope and reconciliation to despair. Their performative silence simultaneously protests and mourns the denunciation, suppression, and erasure of oppositional groups. In this paper, I apply a methodological cluster comprising concepts from ecocriticism, microhistorical-discourse analysis, social anthropology, and other disciplinary fields to address the ramifications of Hong Kong’s story as inscribed within protest-related literary and visual and multimedia art productions. Street art performance, handover-themed art exhibitions, Wong King Fai’s video “Umbrella Dance for Hong Kong,” and Samson Young’s sonic multimedia installations appositely illustrate the conundrum addressed.